Efecto de la micorrizacion con Glomus intraradices Schenk & Smith en el crecimiento de Persea americana Mill variedades ettinger y zutano en condiciones de invernadero - Huanca Pesantes, Roiser Ivan (2016)
Persea americana Mill "avocado", is a very important specie at commercial level, therefore new cultivation areas have increasing; as well as, implementing technological bundles to improve the production. The use of arbuscular mycorrhizal fungi (AMF) in several cultivated species, has been used for the purpose of improving their growth and development. In this research, it was proposed, to determine the effect of the mycorrhization with Glomus intraradices Schenk & Smith in the growth of Persea americana Mill varieties ettinger and zutano in greenhouse conditions. Thirty days old plants were inoculated with 0, 0.5, 1, 2 and 4 grams of G. intraradices and evaluated for 120 days, time which determined the percentage of mycorrhization and variables of stem length and stem diameter, number of leaves, root length, fresh and dry weight of root and above ground. The percentage of mycorrhization was 81.33% for the variety ettinger and 89.89% to variety zutano, after 120 days of treatment with Glomus intraradices. Mycorrhization with the AMF, promoted a significant increase in the stem length of Persea Americana Mill during 120 days of treatment, where ettinger variety reached 31.93 cm, and zutano variety 33.70 cm, when they were treated with 2 grams of inoculum. The root of the ettinger variety reached a length of 41.87 cm, fresh weight of 37.83 grams, dry weight of 7.17 grams, and the above ground fresh weight of 29.97 grams, dry weight of 10.37 grams, after 120 days of the inoculation. Key words: Persea americana, Glomus intraradices, mycorrhization, growth.